Mengembangkan Kegiatan Pembelajaran Menarik Pada Pendidikan Matematika Dasar (LKPD) - Winda Mora Pulungan; Rawiyah Fatimatuzzahra; Jesika Nonida Purba; Rahima Khairani Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to design student worksheets (LKPD) that are interesting and effective in the context of basic mathematics education. LKPD is an important tool in learning mathematics that can help students understand concepts and improve their mathematics skills. In this research, we discuss various strategies for designing student worksheets that encourage student involvement, develop a variety of mathematical problems, integrate higher-order thinking methods, and utilize technology. This strategy creates a more engaging, interactive, and relevant learning experience for students, which in turn helps improve their understanding of mathematics. We also explain the importance of connecting mathematics to the real world, using problem-based activities, incorporating collaborative activities, and integrating mathematical games in worksheet. Additionally, we highlight the use of open-ended questions, complex problem-solving problems, and math projects as methods for integrating higher-order thinking in worksheets. Finally, we explore how to best utilize technology, including mathematics education software, mathematics applications, online resources, educational games, interactive simulations, and online learning platforms, to improve the quality of student worksheets. This article aims to provide practical guidance to teachers, educators and researchers in designing effective LKPD to improve mathematics learning at the elementary level.